



 
Hi Matt, The only way I know to break down this expression is to use the multiple angle expressions for sine and cosine.
Simplify the numerator with the sine expression by taking A = B = x and simplify the denominator using A = x and B = 2x. The resulting denominator will have sin(2x) and cos(2x) which you can write in terms of sin(x) and cos(x) using the expressions above. Finally if you use the fact that sin^{2}(x) + cos^{2}(x) = 1 you can write sin(2x)/sin(3x) as a function of cos(x) alone. Harley
I was hoping to understand how sin2x was formed. ie sinx * sinx = sin^{2} x. I didn't find that out.
Can you break 3 cos^{2}(x) * sin(x) = sin(3x) into the steps it would take to bring it back to sin(3x)? Thanks
 


Math Central is supported by the University of Regina and The Pacific Institute for the Mathematical Sciences. 